The Syringe Pump Gas Distribution (SPGD) system: a simple and low-cost method for simulating NH3/15NH3 deposition - Wu, Chunze; Wei, Xing; Zhang, Chenghang; Khan, Saima (Frontiers in Plant Science, 2025)
Ammonia (NH3) in the atmosphere plays a crucial role in the global nitrogen cycle. Elevated NH3 deposition can result in various detrimental ecological and environmental consequences. Traditionally, researchers have employed methods such as static fumigation, dynamic fumigation using high-precision mass flow meters or standard gas cylinders, and free air enrichment to investigate vegetation responses to NH3 deposition. However, these approaches may suffer from inaccuracies, high costs, or technical complexity. In order to address this issue, we developed the Syringe Pump Gas Distribution (SPGD) system, a cost-effective new method for simulating NH3/15NH3 deposition. This system allows for precise and stable mixing of NH3/15NH3 stored in a syringe with air using a microinjection pump. The resulting mixture is then utilized to simulate NH3/15NH3 deposition. With just one 20 ml syringe, a single SPGD system can simulate NH3 deposition flux ranging from 0 to 31.74 mg N m-2 d-1 (equivalent to 0 - 116 kg N ha-1 yr-1) over an area of 0.36 m2. The SPGD system demonstrated reliability and stability during a 21-day simulated deposition test on potted Populus cathayana under greenhouse conditions (including simulated rainfall). It exhibited adequate adjustment resolution to generate environments with varying NH3 concentrations, corresponding to different NH3 deposition fluxes. The test findings indicated a positive correlation between the δ15N levels in P. cathayana leaves and the NH3 deposition flux increase. The cost, complexity, and risk associated with simulating NH3 deposition can be significantly decreased by utilizing the SPGD system. The SPGD system is modular (gas supply unit and NH3 supply unit) and can be adapted to different research needs, including for simulating the deposition of NO2, SO2 or mixtures. Adopting this system, researchers can safely and efficiently simulate NH3 deposition or perform 15NH3 labeling, thereby advancing the understanding of physiological and ecological processes associated with plants and even forest ecosystems under gaseous deposition.